2011
DOI: 10.1021/la200250m
|View full text |Cite
|
Sign up to set email alerts
|

In Situ STM Imaging of Bis-3-sodiumsulfopropyl-disulfide Molecules Adsorbed on Copper Film Electrodeposited on Pt(111) Single Crystal Electrode

Abstract: The adsorption of bis-3-sodiumsulfopropyldi-sulfide (SPS) on metal electrodes in chloride-containing media has been intensively studied to unveil its accelerating effect on Cu electrodeposition. Molecular resolution scanning tunneling microscopy (STM) imaging technique was used in this study to explore the adsorption and decomposition of SPS molecules concurring with the electrodeposition of copper on an ordered Pt(111) electrode in 0.1 M HClO(4) + 1 mM Cu(ClO(4))(2) + 1 mM KCl. Depending on the potential of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
(67 reference statements)
1
18
1
Order By: Relevance
“…However, if an organic molecule contains an SO 3 − end group but no adsorbing group, such as HS− or −S−S−, it will have no accelerating effect on copper electrodeposition. 40 Numerous studies 21,25,33,37,38,[54][55][56][57][58][59] have confirmed that, when SPS and MPS function as accelerators for copper electrodeposition in the presence of chloride ions, the chemical adsorption of the thiol group to the copper surface is the rate-determining step, as follows:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if an organic molecule contains an SO 3 − end group but no adsorbing group, such as HS− or −S−S−, it will have no accelerating effect on copper electrodeposition. 40 Numerous studies 21,25,33,37,38,[54][55][56][57][58][59] have confirmed that, when SPS and MPS function as accelerators for copper electrodeposition in the presence of chloride ions, the chemical adsorption of the thiol group to the copper surface is the rate-determining step, as follows:…”
Section: Resultsmentioning
confidence: 99%
“…4b, because the trans conformation of the adsorbed TBPS, SPS, and MPS can transform into a gauche conformation. 45,46,49,50,[57][58][59][61][62][63] After this process, the dehydrated Cu 2+ ions easily accept electrons from the chloride ions through an inner-sphere electron-transfer mode. 64 The gauche conformation of the adsorbed TBPS, SPS, and MPS will return to the trans conformation after Cu 2+ exchange and to trap hydrated Cu 2+ ions again, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When developing a high quality TSV electroplating process, it is crucial to solve any problems relating to the parameters of the seed layers, solution, equipment and so on. However, only a few experimental results [15,16,17,18,19,20,21] have been reported on the effect of the parameters of seed layer sputtering and electroplating profiles on the quality of the filled copper, which has led to difficulty in optimizing the filling percentage in vias. For seed layer preparation, Song et al [15] studied the novel deposition with an atomic layer deposition and electroless seed deposition, which showed significant potential for the higher aspect ratio of TSVs.…”
Section: Introductionmentioning
confidence: 99%
“…This was assisted with pulsed power as the experimental power source and additive concentrations as the electroplating solution [19]. Analyses of the process, including cyclic voltammetry (CV) and in situ molecular resolution scanning tunneling microscopy (STM) techniques, have been utilized to illustrate the electroplating procedure [20,21]. It can be summarized that the above mentioned improvements rely mainly on the advanced equipment being complicated to operate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Within the context of our present interest of copper electrodeposition, scanning tunneling microscopy (STM) has been used to examine Cu deposition on gold electrodes with and without organic additives since the early 1990's. It is shown that surface defects of steps and vacancies are the preferred sites for Cu nucleation.…”
mentioning
confidence: 99%